Edukasi Pencegahan Anemia pada Remaja Putri di PPTQ Al-Rasyid Kartasura: Anemia Prevention Education for Adolescent Girls at PPTQ Al-Rasyid Kartasura - Kusumaningrum, Tanjung Anitasari Indah; Sandrana, Sabrina Cantika Putri; Rini, Novyanti Setiyo; Pertiwi, Nanda Hani Nur; Priska, Maria Alna; Nabila, Nurjihan Luthfia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Adolescents experience a very dynamic period of physical development. Anemia is one of the problems experienced by young women. If iron intake in adolescent girls is insufficient, adolescents can experience problems with their needs and immune response. One of the causes of anemia in teenagers is a lack of knowledge about anemia. This service activity was for young women at the Tahfidz Quran Al-Rasyid Kartasura Islamic Boarding School. This service aims to educate young women about anemia to prevent anemia. The method for implementing this service program is to provide counseling, starting with a pre-test, delivering material and interactive discussions, and ending with a post-test. The results achieved from this service activity were increased teenagers' knowledge about anemia before and after the counseling. This shows the importance of health education or promotion to be carried out continuously to teenagers. Knowledge has a vital role in shaping a person's actions. It is hoped that teenagers with good knowledge about anemia can prevent anemia in themselves because it will affect learning ability and concentration, inhibiting the growth of both body and brain cells. Therefore, teenagers can increase their understanding of anemia through various media and improve their lifestyle.